Auricular Acupuncture for Treatment of Preoperative Anxiety in Patients Scheduled for Ambulatory Gynaecological Surgery: A Prospective Controlled Investigation with a Non-Randomised Arm. Issue 4 (August 2018) - Wunsch, Jakub K; Klausenitz, Catharina; Janner, Henriette; Hesse, Thomas; Mustea, Alexander; Hahnenkamp, Klaus; Petersmann, Astrid; Usichenko, Taras I
Objective: Auricular acupuncture (AA) is a promising alternative treatment for situational anxiety. The aim of this pilot investigation was to test the acceptability and feasibility of AA as a treatment for preoperative anxiety (PA) in preparation for a subsequent randomised controlled trial. Methods: AA was offered for treatment of PA to female patients who were scheduled for ambulatory gynaecological surgery. In patients who agreed, indwelling fixed needles were applied bilaterally at the points MA-IC1, MA-TF1, MA-SC, MA-AH7 and MA-T the day before surgery. Patients who declined AA but agreed to be examined constituted the control group (no intervention). State anxiety (primary outcome) was measured using the State-Trait-Anxiety Inventory (STAI) before AA (time I), the evening before surgery (time II) and immediately before surgery (time III). Anxiety was measured with a 100 mm visual analogue scale (VAS-100); heart rate, blood pressure and serum cortisol were also quantified. Results: Data from 62 patients (32 with AA and 30 with no intervention) were analysed. Whereas preoperative anxiety was reduced after AA the evening before surgery (P<0.01), anxiety levels in the control group increased from the first to the last measurement (P<0.001). Secondary outcomes were comparable between the patients from both groups. Conclusions: AA was acceptable and feasible as a treatment for preoperative anxiety. The results were used for the sample size calculation of a subsequent randomised controlled clinical trial. Trial Registration Number: NCT02656966; Results.